2010
DOI: 10.1007/978-3-642-17746-0_13
|View full text |Cite
|
Sign up to set email alerts
|

Compact Representation of Large RDF Data Sets for Publishing and Exchange

Abstract: Abstract. Increasingly huge RDF data sets are being published on the Web. Currently, they use different syntaxes of RDF, contain high levels of redundancy and have a plain indivisible structure. All this leads to fuzzy publications, inefficient management, complex processing and lack of scalability. This paper presents a novel RDF representation (HDT) which takes advantage of the structural properties of RDF graphs for splitting and representing, efficiently, three components of RDF data: Header, Dictionary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 13 publications
0
45
0
Order By: Relevance
“…HDT) to the results. HDT [6] achieves a greater compression for most of the datasets we experimented on. Such high performance can be attributed to its ability to take advantage of the highly skewed RDF data.…”
Section: Comparison Using Compressed Dataset Sizementioning
confidence: 99%
See 4 more Smart Citations
“…HDT) to the results. HDT [6] achieves a greater compression for most of the datasets we experimented on. Such high performance can be attributed to its ability to take advantage of the highly skewed RDF data.…”
Section: Comparison Using Compressed Dataset Sizementioning
confidence: 99%
“…[5] has explored various compression techniques for RDF datasets and observed that most RDF datasets are highly compressible due to it's power-law distribution in term-frequencies, schemas and resources. [6] introduced a more compact representation format, HDT, by decomposing an RDF data source into Header, Dictionary and Triples. A specific compressed version of HDT, HDT-compressed, outperforms most of the universal compressors [6].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations